TOURMALINE FROM LATE QUARTZ VEINS OF THE MURTYKTY GOLD DEPOSIT, REPUBLIC OF BASHKORTOSTAN - M.A. Rassomakhin; E.V. Belogub; K.A. Novoselov; P.V. Khvorov (Минералогия)
Tourmaline, an intermediate member of the oxyschorl–oxydravite–oxymagnesio-foitite-bosiite series with a predominance of the oxy-dravite-bosiite end-member, was studied from late calcitequartz veins in the eastern zone of the Murtykty gold deposit (Republic of Bashkortostan). Sulfide mineralization in veins includes rare chalcopyrite, pyrite, sphalerite and galena. Accessory minerals are xenotime-(Y), vanadium-containing rutile and fine high-fineness gold. Supergene mineralization resulted from decomposition of carbonates, sulfides and rock-forming silicates includes kaolinite, hydroxides of Mn (chalcophanite, psilomelane) and Fe (goethite and limonite ochers), mainly developed in vein cavities ; chalcopyrite is replaced by cuprite and malachite. The composition of tourmaline is close to metamorphic dravite of orogenic gold deposits and tourmaline of gold-porphyry deposits, transitioning from porphyry to epithermal. Two possible B sources for the formation of tourmaline are considered: sedimentary rocks of the paleoisland-arc complex and granodiorites of the Mansurovo pluton.